Bibliotherapy Programmes in Dublin Public Libraries: A Case-Study of Dublin City, Fingal and South Dublin Public Library Services. - Hutchinson, Emma (Qualitative and Quantitative Methods in Libraries; 2014: Special Issue: Social Justice, Social Inclusion, 2017)
Approximately one in four people suffer from mental health problems during the course of their lives, yet mental health is a taboo subject of which many people are ashamed (Department of Health, 2011). The aim of this research was to investigate bibliotherapy services in Dublin’s public libraries in order to discover best-practice for implementing a therapeutic reading programme in a public library environment.